Exploiting behavioural insights to foster global cooperation - Gianluca Grimalda; Simon Bartke; Steven Bosworth; Andreas Friedl; Katharina Lima de Miranda; Patrick Ring; Dennis J. Snower (Kiel Institute for the World Economy (IfW), 2017)
The authors identify three challenges to global cooperation and propose three solutions. The first is the lack of integration of civil society into global governance. In the spirit of Ostrom's poly-centric governance, they propose stronger interaction between public international authorities, including the G20, and civil society. The second is the reliance of economic policy on a model of human behaviour based on self-interest and instrumental rationality. The authors propose on the contrary to ground policies on behavioural evidence, and to increase cooperation between academic institutions active in this field worldwide. The third is the recognition that the spread of divisive narratives, which emphasize demarcations across national or religious lines, hinders global cooperation. Alternative narratives should be produced within a transformative process involving responsible leaders, decision-makers, experts, and civil society.
Keywords: D04; D91; H41; 330; behavioral economics; cooperation; civil society; narrative